Amiodarone-associated bilateral vestibulopathy - Gürkov, Robert; Schell, Angela (European archives of oto-rhino-laryngology and head & neck, 2018)
BackgroundBilateral vestibulopathy (BVP) is a debilitating disorder characterized by the hypofunction of both vestibular end organs or nerves. The most frequent identifiable causes of BVP are ototoxic drug effects, infectious and autoimmune disorders. The majority of cases, however, remain idiopathic.MethodsMedical records of patients diagnosed with idiopathic BVP were examined in five dizziness clinics.ResultsWe identified 126 patients with “idiopathic” BVP. Out of these, 15 patients had a history of Amiodarone treatment before the diagnosis of BVP, resulting in a 12% prevalence.ConclusionThe present report supports the hypothesis that Amiodarone can cause BVP. Vestibular examination in patients taking Amiodarone and suffering from balance-related symptoms are recommended, to recognize this adverse effect as early as possible and allow for an informed judgement on a potential dose reduction or withdrawal for recovery of the vestibular function.
Published online: 27 December 2017
Gesehen am 16.05.2019